Effect of PGF2α and Methylergometrine during Puerperium in Gir Cows - Solanki, GB; Chaudhary, JK; Vijyeta, HP; Gamit, PM; Parikh, SS (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The therapeutic efficacy of methylergometrine and PGF2α on uterine involution and postpartum fertility was studied in 18 (6/group) Gir  cows. Animals of groups I and II were treated with single i/m injection of PGF2α and Methylergometrine immediately after parturition,  respectively, while group-III served as untreated control. The time required for expulsion of fetal membranes was shorter in group-I  (2.55 ± 0.60 hours) than in group II (3.03 ± 0.34 hours) and group III (4.10 ± 0.36 hours) but did not differ statistically. Time taken for  completion of uterine involution was significantly (p
Keywords: Methylergometrine; PGF2α; Expulsion of placenta; Uterine involution; Service period